1995
DOI: 10.1007/bf02208146
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocalcinosis: Sonographic study of the knee

Abstract: Summary Sonography of the knee was performed in 28 patients with chondrocalcinosis and in 46 normal subjects. In each joint the authors examined synovial membrane, articular cartilage of femoral condyles, synovial fluid and menisci; they also searched for Baker's cysts. A significant thickening of synovial membrane was present. In 43 joints sonography showed linear hyperechoic images within condylar cartilage; they were parallel to bone surface and were interpreted as calcifications because of the coincidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…[6][7][8][9] In this paper we tried to define the US aspect of CPPD calcifications in order to propose ultrasonographic criteria for the differentiation of CPPD deposits and hyperechoic deposits of another nature. We then tried to verify the relationship between the ultrasonographically defined presence of CPPD calcifications in cartilage and periarticular tissues and the presence of CPPD crystals in the synovial fluid and compare the US findings with the radiographic findings.…”
mentioning
confidence: 99%
“…[6][7][8][9] In this paper we tried to define the US aspect of CPPD calcifications in order to propose ultrasonographic criteria for the differentiation of CPPD deposits and hyperechoic deposits of another nature. We then tried to verify the relationship between the ultrasonographically defined presence of CPPD calcifications in cartilage and periarticular tissues and the presence of CPPD crystals in the synovial fluid and compare the US findings with the radiographic findings.…”
mentioning
confidence: 99%
“…49 US is effective also in demonstrating calcium pyrophosphate deposits in chondrocalcinosis (CPPD). In 1995, Coari et al 50 showed the presence of calcification within condylar cartilage in 43 knees of 28 patients with CPPD, results confirmed by Foldes 51 and lately by Sofka et al, 52 who described a case of US-detected meniscal calcification not visualized by conventional radiography. The US criteria for the diagnosis of CPPD deposition were proposed by 2 distinct groups: Grassi et al 44 focused their attention on the different pattern of crystal deposition in gout and CPPD disease, showing that the presence of hyperechoic material within the substance of hyaline cartilage is typical of chondrocalcinosis.…”
Section: Us In Crystal-related Arthropathiesmentioning
confidence: 88%
“…Over the last decade US has been used increasingly for the diagnosis of CPPD in the joints, and the main US findings have been described extensively by us and other authors [1–8]. The main US landmark of the disease is the presence of hyperechoic deposits, not creating posterior shadowing, in the hyaline cartilage and in the fibrocartilage of joints (menisci, triangular fibrocartilage of the wrist) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, ultrasonography (US) has been demonstrated to be an excellent technique for detecting calcium pyrophosphate dihydrate (CPP) crystal deposits in joints and periarticular tissues [1–8], and the aspect of these deposits in hyaline cartilage and fibrocartilage has been described (Figure 1). In the literature the sensitivity of US in identifying CPP crystal deposits varies between a minimum of 15% [3] for the plantar fascia and a maximum of 89% [7] for the hyaline cartilage of the knee.…”
Section: Introductionmentioning
confidence: 99%